Lu Ann Homza (2022). Village Infernos and Witches’ Advocates: Witch-Hunting in Navarre, 1608-1614. - Ortiz, Alberto (Edad de Oro, 2023)
Lu Ann Homza (2022). Village Infernos and Witches’ Advocates: Witch-Hunting in Navarre, 1608-1614. Pennsylvania: The Pennsylvania State University Press, 248 pp. [ISBN 978-02-71-09181-5].